ARSITEKTUR BANGUNAN GEREJA SUMBER KASIH DI KELURAHAN KANDAI, KECAMATAN KENDARI, KOTA KENDARI - ishak kadir; La Ode Muhammad Ilham; salniwati salniwati (SANGIA: Jurnal Penelitian Arkeologi, 2020)
This study describes the architecture of the Sumber Kasih Church building in Kendari District, Kendari City. The purpose of this study is about the characteristics of the Sumber Kasih Church building, influencing factors in church architecture, and church architectural style. This study uses a study of architectural concepts and tropical architecture. This research is a descriptive qualitative type with inductive reasoning using architectural, stylistic, and morphological analysis as supporting analyzes in this research. Based on this research, it can be concluded that the Sumber Kasih Church building has uniform and simple characteristics. The characteristics of this building can be found on the church roof which is in the shape of a saddle, the shape of the gable roof is made with a slope of 40Âº to function as to drain the falling rainwater. The gable shape of this church is also often found in the houses of local people. Based on the factors that influence the architectural form, the Sumber Kasih Church building is influenced by two factors, namely cultural factors and climatic factors. Based on its architectural form, Sumber Kasih Church is influenced by tropical architectural styles and traditional architecture of the local culture.